2021
DOI: 10.1007/s41062-021-00694-8
|View full text |Cite
|
Sign up to set email alerts
|

Utilisation of waste glass powder to improve the performance of hazardous incinerated biomedical waste ash geopolymer concrete

Abstract: A mixture of hazardous waste from various places, including hospitals, testing facilities, clinics, etc., is a biomedical waste. It is possible that eventually, there could be a significant risk to human lives and the survival of plant and animal life on this planet from hazardous biomedical waste disposal. Biomedical waste is usually burnt at an incineration plant and produces ash called incinerated biomedical waste ash (IBWA). If IBWA is not disposed correctly, it may contaminate the groundwater because heav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…Stronger and denser materials are produced when sodium hydroxide concentrations are raised from 8 to 16 M (Kumaravel and Sivakumar 2018 ; Farhan et al 2018 ; Abbass and Singh 2021a ; Gunasekara et al 2015 , 2016 ). The micro-filler effect of BMW is also responsible for the high density of the mixes as it is suggested that the use of 30% BMW as replacement of GGBFS in GPC has resulted in high density (Suresh Kumar et al 2022a , 2022b , 2022c , 2023 ; Arunachalam et al 2022 ). The enhanced density is also reported, when the replacement of fly ash in GPC by 30% waste wood ash is done (Arunkumar et al 2023 , 2021 , 2022a , 2022b ; Arun et al 2022 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Stronger and denser materials are produced when sodium hydroxide concentrations are raised from 8 to 16 M (Kumaravel and Sivakumar 2018 ; Farhan et al 2018 ; Abbass and Singh 2021a ; Gunasekara et al 2015 , 2016 ). The micro-filler effect of BMW is also responsible for the high density of the mixes as it is suggested that the use of 30% BMW as replacement of GGBFS in GPC has resulted in high density (Suresh Kumar et al 2022a , 2022b , 2022c , 2023 ; Arunachalam et al 2022 ). The enhanced density is also reported, when the replacement of fly ash in GPC by 30% waste wood ash is done (Arunkumar et al 2023 , 2021 , 2022a , 2022b ; Arun et al 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…The enhanced density is also reported, when the replacement of fly ash in GPC by 30% waste wood ash is done (Arunkumar et al 2023 , 2021 , 2022a , 2022b ; Arun et al 2022 ). The use of waste glass powder along with BMW in GPC has resulted in compact bonding ultimately resulting in high density of GPC mixes (Suresh Kumar et al 2022b , 2022c ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of pozzolonic materials in the manufacture of concrete has a long history. Metakaolin (MK) [1,2,18], Fly Ash (FA) [3,4], Ground Granulated Blast Furnace Slag (GGBFS) [5,6], Low Calcium Wood Ash (LCWA) [7,8], Biomedical Waste Ash (BWA) [9,10], E-Waste [11,12], Silica Fume (SF) [1,13,21,23,24], Glass Powder (GP) [Suresh ) [14,15], Palm Oil Fuel Ash (POFA) [16] and Rice Husk Ash (RHA) [17]. Manufacturing wastes, including fly ash, metakaolin, silica fume, blast furnace slag, and rice husk ash, are the most prevalent pozzolans utilized globally.…”
Section: Introductionmentioning
confidence: 99%